Pengaruh Pemberian Pupuk NPK terhadap Pertumbuhan Bibit Mangrove pada Media Tanam Hydraquent di Yayasan Mangrove Institute Aceh Jaya - Kasmila, Puja; Mursawal, Asri (Universitas Teuku Umar, 2023)
The destruction of mangrove forests reduces forest area and mangrove plant species. Mangrove forest restoration requires seeds with good growth and are resistant to pests and diseases. The purpose of this study was to determine the effect of NPK fertilizer application on mangrove seedlings growth in the Hydraquent Garden media at the Aceh Jaya Mangrove Institute Foundation. The research was conducted on September 2022. The tools and materials used in this research were R. apiculata mangrove seeds, soil hydraquent, meter, tools, cutter, wood stake, refractometer, and thermometer. This research used a descriptive method in which it only took the average value of mangrove seedlings growth. There were four types of observations given to mangrove seedlings, namely T0 (no fertilizer), T1 (giving 3 gr of fertilizer), T2 (6 gr), T3 (9 gr) and T4 (12 gr). Based on observations, NPK fertilizer on Hydraquent soil was proven to increase plant height and number of leaves.